REAKSI PASAR MODAL TERHADAP KEBIJAKAN TAX AMNESTY PADA SAAT PENGUMUMAN DAN AKHIR PERIODE I - Sanjiwani, Putu Diah Aryastuti; Jati, I Ketut (E-Jurnal Akuntansi, 2017)
Tax amnesty policy events will lead market to quickly respond the information that makes the stock market be more sensitive to the surrounding events. This study aims to examine and analyze the reaction of investors to the tax amnesty policy events during the announcement and the end of the first period. This research was conducted in companies incorporated in the ILQ-45 at Indonesian Stock Exchange. The samples are 44 companies, with a purposive sampling method. The analysis technique that used are paired sample t-test and the wilcoxon signed rank test. The results are there are not any differences in average abnormal return obtained by investors at the time before and after the tax amnesty policy events during the announcement and the end of the first period. The hypotheses are rejected due to the short observation period and the resulst are still lack of public knowledge about the tax amnesty policy.
Keywords: abnormal return, tax amnesty, market reaction